Pantauan Prediktif Covid-19 Dengan Menggunakan Metode SIR dan Model Statistik Di Indonesia - Sabita, Hary; Herwanto, Riko (Politeknik Negeri Sriwijaya, 2020)
During the COVID-19 pandemic, many attempts have been made to predict cases of additional patients, deaths and other medical indicators using various methods. Several forecast projects and predictions have influenced policies in several countries, including Indonesia. However, predictions and predictions for the COVID-19 pandemic are inherently uncertain. Uncertainty is rooted in a lot of the unknown. Starting from the virus itself, complexity, heterogeneity, human behavior, protocols and government intervention. In this study we explored the potential using the term